i wanted to ask for a clarification.

I was looking around in my linear algebra text when i reached this justification:

Considered two coloumn vectors $X$ and $Y$, and assume $$X ^tC Y = X^t C^t Y$$ for every $X,Y \in V$, with $V$ an $n$-dimensional vectorial space, with $X^t, Y^t$ being the transposed of $ X, Y$.

My book says that because of this is valid for every $X,Y$, we can deduce: $$ C^t = C$$

Now, it is intuitively true, but i was wondering if ,maybe the general sum (it's a bilinear form) could equals without needing $C^t = C$. I've seen this type of justification also in other theorems, but i want to know if there is a way to prove it formally, beacuse i'm not satisfied.

Thanks in advance.

  • 2
    $\begingroup$ See what happens if $X=e_i$ and $Y=e_j$ ($i$-th and $j$-th standard basis vectors of $V$). $\endgroup$ Oct 23 at 0:32
  • 1
    $\begingroup$ What does this have to do with the “null” in the title? $\endgroup$ Oct 23 at 0:40
  • $\begingroup$ The transpose of a linear transformation doesn’t make sense over a general vector space. But it does make sense if the vector space is given an inner product. $\endgroup$ Oct 23 at 0:43
  • $\begingroup$ Sorry, language translations $\endgroup$ Oct 23 at 0:45

since these are column vectors, evidently $V=\mathbb F^n$

select $n$ linearly independent vectors $\mathbf x_k$ and $n$ linearly independent $\mathbf y_k$ (if you like you can set $\mathbf y_k:=\mathbf x_k$)

Then for $k,j \in \big\{1,2,...,n\big\}$
$\mathbf x_k^T C\mathbf y_j=\mathbf x_k^T C^T\mathbf y_j$
$\implies\mathbf x_k^T\big( C-C^T\big)\mathbf y_j = \mathbf 0$
$\implies \mathbf X^T\big( C-C^T\big)\mathbf Y = \mathbf 0$
where $\mathbf X$ and $\mathbf Y$ have column $j$ given by $\mathbf x_j$ and $\mathbf y_j$ respectively. But $\mathbf X$ and $\mathbf Y$ are invertible,
$\implies \big( C-C^T\big) = \mathbf 0$
$\implies C=C^T$


Setting $A = C-C^t$ you have $X^tAY=0$ for all $X,Y$. Let $e_j$ denote the $j$-th standard basis vector. The $(i,j)$-th entry of $A$ can be expressed as $e_i^tAe_j$. But this is zero, hence $A=0$, i.e., $C^t = C$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.